Relevance of objective and subjective profile: creative behavior assessment in higher education students - Alvarez-Icaza, Inés; Suárez-Brito, Paloma; Alvarez, Jaime; Molina-Espinosa, José Martín (Frontiers in Education, 2024)
Creativity is a 21st Century skill. Promoting problem-solving and attending to global complex issues in formative learning experiences and professional endeavors is considered necessary. The assessment of creativity in higher education is a challenge itself due to few objective instruments for Spanish speakers and Latin populations considering this skill as key for current and future challenges. In addition to formal creativity training, which is based on curricula formed by a set of tools and processes, there is also the role of self-perception over this skill. The objective profile is the expected performance, while the subjective is seen as a self-declared ability. In this sense, having a proper assessment of creative behavior allows to align the intentions of institutions and educators toward an integrated professional profile in a multidisciplinary manner. In this study, the Creative Behavior Assessment Instrument was applied to pre-graduates from Creative Studies (CS) (Design, Architecture, Digital Animation, and Communication) areas and other disciplines to answer three main research questions (1) Are CS students more creative than other discipline students?; (2) How does fluency vary between students from different disciplines?; (3) Is there coherence between the objective and subjective responses to the instrument? The methodological approach for this study is mixed methods, focusing on total score, visuospatial ability, fluidity, and self-perception. Results are discussed in terms of the difference shown by the students' objective/subjective profiles in relation to their discipline, the relevance of promoting creativity in higher education, and the implications of individual differences regarding the subjective profile.